Abdominal compartment syndrome – Intra-abdominal hypertension: Defining, diagnosing, and managing - Papavramidis, Theodossis S (Medknow Publications, 2011)
Abdominal compartment syndrome (ACS) and intra-abdominal hypertension (IAH) are increasingly recognized as potential complications in intensive care unit (ICU) patients. ACS and IAH affect all body systems, most notably the cardiac, respiratory, renal, and neurologic systems. ACS/IAH affects blood flow to various organs and plays a significant role in the prognosis of the patients. Recognition of ACS/IAH, its risk factors and clinical signs can reduce the morbidity and mortality associated. Moreover, knowledge of the pathophysiology may help rationalize the therapeutic approach. We start this article with a brief historic review on ACS/IAH. Then, we present the definitions concerning parameters necessary in understanding ACS/IAH. Finally, pathophysiology aspects of both phenomena are presented, prior to exploring the various facets of ACS/IAH management.